A gestão estratégica na administração pública brasileira diante da influência do New Public Management e da adoção do Balanced Scorecard: o caso da Receita Federal Do Brasil - Blonski, Fabiano (2012)
The 70's and 80's of the last century saw the emergence of a wave of thought in public administration aimed to break with the bureaucracy and classical approach with concepts from the private sector, as a response to the crisis scenario installed in several countries. From this movement came the New Public Management, which largely influenced the structural reforms implemented in the Brazilian State during the 90’s. These reforms resulted into a State that, in theory, has efficiency as one of its fundamental principles. The quest for efficiency has required a greater focus on the strategic management of the government and its agencies, rather than the mere maintenance of the state structure. Moreover, the measurement of efficiency necessarily involves a measure of performance, which is quite distinct in the government when compared to the predominant focus on financial results that exists in the private sector. It is necessary, therefore, to use a management tool capable of realizing the different dimensions of state activity. The Balanced Scorecard is presented as suitable to the task, allowing not only the measurement of State’s performance, but also helping the design and implementation of its strategy. Given this context, the present study pursued to understand, through a case study in the Receita Federal do Brasil, how works the Strategic Management at the Brazilian federal government, considering the combination of the precepts of the New Public Management and the Balanced Scorecard.